Structural Behaviour of Prestressed Concrete Hollow Beams - Mohamad Zin, Rosli (1993)
This thesis is concerned with the primary objective of studying the structural behaviour of prestressed concrete hollow beams. Ten simply supported rectangular hollow beams and one rectangular solid beam were tested on an effective span of 2.80m subjected to two third point loadings. The variables in the study were the percentage of self weight reduced and the amount of prestressing wires. Eight beams were tested unbonded while the other two beams were fully bonded.Ultimate loads, cracking loads, crack widths and deflections were recorded at various loadings and crack propagations were observed. The results obtained were compared with theoretical values. It was observed that due to the absence of material in the hollow portion, compared to a solid beam with similar outside dimensions, the ultimate moment carrying capacity of prestressed hollow beam is reduced if neutral axis of the beam at failure is located below the top flange. However, if the neutral axis of the beams at failure is located within the top flange, then the ultimate moment carrying capacity is at least equivalent to that of a solid beam. It was also observed that the theory on the ultimate moment carrying capacity presented in this thesis gives a fairly good prediction. However, the theory used to predict cracking load as well as deflection was found not suitable for unbonded beams as it greatly underestimates the deflection and overestimates the cracking load. It was also observed that bonding has a great influence on crack widths and deflections. Bonded beams show more uniform crack distribution with reduced maximum crack width and increased ultimate load capacity. From test results, it is recommended that prestressed hollow beams should be made bonded in order to achieve at least the predicted cracking load.